(3GdEjbGX ef GdLYLYI HGdHQgGf Ydi GdQLYIs - (3GdYGedj, GdMQ, eMeO Hf GdMSf Hf Ydj, J (B1104(3g`s
(3ChdgG (B:s
(3GdMeO ddg eMjj GdCehGJ heejJ GdCMjGA(B...(3ajbhd GdabjQ(B... (3bO LeY HYV GdSGOGJ(B... (3QSGdI aj EKHGJ GdQLYI GdJj hYOgG Gddg HgG GdeDefjf (B... (3hajgG CTjGA ZQjHI eSJHYOI(B...s
(3BNQgG (B:s
(3dh CQOJ GdBf dCVaJ Edi CMGOjK gPg GdQSGdI eG jRjO YdjgG aj GdYOO aJJVGYa GdCMGOjK dCfj de Cfbd ef QSGFd GdeJCNQjf TjFG (B... (3hdG CXf TjFG ef eSGFd GdCUhd hGdaQhY jhLO ajg ef GdfUhU CcKQ ef gPg GdeSCdI(B. (3hGddg Gdehabs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B90s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds